2021
DOI: 10.1002/sres.2818
|View full text |Cite
|
Sign up to set email alerts
|

Using soft systems methodology to align community projects with sustainability development in higher education stakeholders' networks in a Brazilian university

Abstract: The purpose of this paper is to report on the use of the soft systems methodology (SSM) to enhance the role of the higher education institution (HEI) stakeholder's action networks in achieving the sustainable development goals (SDGs). We review the literature on sustainable development in HEIs, in particular the role of stakeholder networks for the implementation of SDGs in HEI. We outline some of the features of SSM as an approach to help make sense of this complexity. CATWOE analysis, a conceptual SSM tool, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…This result could be attributed to the expectation that managers’ communication schemes often do not fully consider employees’ training, personal traits and capabilities (Shin et al , 2022). Consistent with Paucar-Caceres et al (2022), these results may also indicate that communication mechanisms are not adequately incorporated to reduce failures. Consequently, the absence of these mechanisms may generate confusion as the employees may need to consider messages related to reliable strategies.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…This result could be attributed to the expectation that managers’ communication schemes often do not fully consider employees’ training, personal traits and capabilities (Shin et al , 2022). Consistent with Paucar-Caceres et al (2022), these results may also indicate that communication mechanisms are not adequately incorporated to reduce failures. Consequently, the absence of these mechanisms may generate confusion as the employees may need to consider messages related to reliable strategies.…”
Section: Resultssupporting
confidence: 53%
“…The above review briefly introduced some approaches to investigating ESI from a systemic perspective. In this sense, Paucar-Caceres et al (2022) indicated that the most frequently used tools include SSM (Checkland, 2001), the viable system model (Martinez-Lozada and Espinosa, 2022), system dynamics (Sánchez-García et al , 2023), network analysis and multicriteria methods (Saaty, 2004; Adeoye et al , 2021; Jaiswal et al , 2021). In this context, SSM has been helpful as a heuristic for identifying significant actors in terms of ESI, secondary but necessary actors, and uncovering pathological relationships to build a mental model of how a change in pathological relationships can be generated (Núñez-Ríos et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In formulating expert opinions, this study used a conceptual model development system as shown in Figure 2. This system is a development of Soft Systems Methodology (SSM) [42][43][44][45][46] and System Development Life Cycle (SDLC) [47][48][49][50].…”
Section: Methodsmentioning
confidence: 99%